LIVING IN THREE WORLDS: A RELATIONAL HERMENEUTIC FOR THE DEVELOPMENT OF A CONTEXTUAL PRACTICAL THEOLOGICAL APPROACH TOWARDS A MISSIONAL ECCLESIOLOGY - Smit, Guillaume Hermanus (Scriptura, 2015)
This article argues for an integrated paradigmatic approach to conducting practical theological research. This integration is prompted by the researcher’s experience as theologian in a culturally diverse community where theologies from different perspectives share the same ecclesial landscape. Three primary thought paradigms are discussed as a frame of reference for this integration. These are the pre-modern paradigm, the modern paradigm and the postmodern paradigm. A relational hermeneutic is proposed that utilises the story of Scripture as told through the centuries and strives to share God’s mission to the world. This relational hermeneutic could serve as the integrational focal point of ministry practice that spans theological viewpoints.